Effect of Ethyl Acetate Fraction of P. amarus Leaf on Hematological and Biochemical Parameters in Albino Rat with Arsenic Induced Toxicity - Ujah, Frederick O; Y. Mohammad, Yusuf; E. Audu-War, Vera (Asian Journal of Pharmaceutical Research and Development, 2021)
Therapeutic effect of ethyl acetate fraction of P. amarus leaf was probed on hematological and biochemical indices in albino rats induced with arsenic poison. Acute toxicity of 100% ethyl acetate fraction was evaluated at dose range of 100 to 5000mg/kgbw for 24hrs and no apparent signs of toxicity were observed. However, exposure for 10days, death was observed for dose of 1000mg/kg and above. Thus LD50 of sub-acute toxicity is 707.11mg/kg. Significant decreased in hematological indices observed, indicate alterations that affect the physiology and hematopoiesis of blood by arsenate administered and with normal levels of MCV and MCH, this suggest normocytic anemia. Furthermore, decrease level of HGB could implies that arsenic might have affected the incorporation of hemoglobin in the red blood cells or the morphology and osmotic fragility in red blood cells and this can affect oxygen carrying capacity of blood, although with MCV and RDW both normal, the RBCs are likely the same normal size. Falls in Platelets count with low MPV and irregular morphology as indicated by PDW infer that the bone marrow isn't producing enough new platelets which may result in low clotting capacity of blood. This is not caused by infection from bacteria as procalcitonin (PCT) in all groups showed no significant difference but the effect was that of arsenic poison. WBCs drop significantly, suggesting susceptibility to opportunistic infections. Result also showed increased bilirubin, an indication of cholestasis. However, these effects were significantly (P<0.05) ameliorated in the treatment groups, as levels of these parameters were reversed. Conclusively, this might be as a result of phenolics in P. amarus. Phenolics excite their mechanism of therapeutics either by ways of antioxidant activities as free radical scavengers or chelators of metal ions.